Role of Toll like receptor in progression and suppression of oral squamous cell carcinoma - Yash Sharma; Kumud Bala (Frontiers Media S.A., 2020)
Oral squamous cell carcinoma (OSCC) is one of the most common type of head and neck squamous cell carcinoma and one of the multifactorial process that consists of most contributing factors such as tobacco smoking, chewing and alcohol consumption that altered the intracellular environment. Recent studies have shown relevance of Toll like receptor (TLR) associated with carcinogenesis. This review aim's to explore that how TLR associates with progression and suppression of OSCC. This review is a classical review that has confined to articles published in the past 19 years (i.e. 2000-2019) and has summarized the perspective of the authors. 62 articles were reviewed and it was found that progression and suppression of OSCC is associated with different TLRs promoting tumor development and also inhibiting the progression of oral neoplasm. It was found that TLR2, TLR3, TLR4, TLR5, TLR7 and TLR9 are associated with tumor development i.e. in progression of OSCC, where as suppression of OSCC through TLR3 and TLR7. We authors would like to conclude that literature survey has indicated effective TLR's against OSCC development and can be explored to investigate other TLRs that can be used for therapeutic purposes in near future.